Metabolic changes in groundnut leaf due to infection by leaf spot pathogens - and H.K.L. CHAWLA, S.K. GUPTA, P.P. GUPTA, C.D. KAUSHIK (Indian Phytopathology, 2002)
Changes in specific activities of polyphenol oxidase (PPO) peroxidase (PO), catalase and levels of total phenols, total soluble sugars and mineral elements in the healthy and diseased leaves of susceptible (MH-l, JL-24) and tolerant (MH-2, C-333) cultivars of groundnut were studied. Total phenols were markedly higher in tolerant than in susceptible cultivars. Amount of phenol decreased after infection in all the cultivars, conversely, total soluble sugar increased after infection. The specific activities of PPO remained higher while that of PO was lower in tolerant cultivars than in susceptible ones. In response to infection, the activities of both the enzymes increased sharply. However, this increase was more associated with susceptibility. Catalase activity, however, was observed only in healthy leaves and comparatively higher in tolerant cultivars. Nitrogen (N) content was lower in tolerant than in susceptible cultivars and it decreased after infection. Following infection, phosphorus (P), zinc (Zn) and manganese (Mn) were found to decrease while potassium (K) and iron (Fe) increased in all the cultivars. These changes were quite considerable in susceptible compared with tolerant cultivars.